Endovascular therapy for late-window M2-segment middle cerebral artery occlusion: analysis of the CLEAR study - Winzer, Simon; Kaiser, Daniel P.O.; Qureshi, Muhammad M.; Castonguay, Alicia C.; Strbian, Daniel; Nogueira, Raul G.; Nagel, Simon; Raymond, Jean; Abdalkader, Mohamad; Demeestere, Jelle; Marto, João Pedro; Yamagami, Hiroshi; et al. (Stroke, 2025)
Background: There is uncertainty about whether patients with M2 occlusion benefit from endovascular therapy (EVT) in the late (6-24-hour) time window. We evaluated the clinical outcomes of patients with M2 occlusion selected for EVT compared with those who received medical management (MM) in the late window. - Methods: This multinational cohort study was conducted at 66 sites across 10 countries (January 2014 to May 2022). We included consecutive patients with late-window stroke due to M2 occlusion, baseline National Institutes of Health Stroke Scale score of ≥5, and premorbid modified Rankin Scale score of ≤2 who received EVT or MM alone. The primary end point was 90-day ordinal shift in the modified Rankin Scale score. Safety end points were symptomatic intracranial hemorrhage and 90-day mortality. Differences in outcomes were determined using inverse probability of treatment weighting-adjusted logistic regression models. - Results: Among 5098 patients, 496 met inclusion criteria (median [interquartile range] age, 74 years [62-81 years]; baseline National Institutes of Health Stroke Scale score, 12 [8-17]), of whom 394 (79.4%) received EVT and 102 (20.6%) MM. In inverse probability of treatment weighting adjusted analyses, there was no favorable 90-day ordinal modified Rankin Scale shift (odds ratio, 1.39 [95% CI, 0.92-2.12]) and no difference of functional independence rates (modified Rankin Scale score of 0-2; odds ratio, 1.72 [95% CI, 0.93-3.15]) with EVT compared with MM. Moreover, symptomatic intracranial hemorrhage risk (odds ratio, 3.46 [95% CI, 0.50-23.92]) and 90-day mortality (odds ratio, 1.11 [95% CI, 0.66-1.87]) were not statistically different between treatment groups. - Conclusiions: In patients with M2 occlusion in the 6- to 24-hour time window, there was no difference in disability outcomes or symptomatic intracranial hemorrhage risk between patients treated with EVT compared with MM. Results of ongoing randomized trials will provide further insight. - Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT04096248.